Evaluation Of Pulmonary Functions Of Off-Pump Coronary Artery Bypass Graft Patients (KYAMC Journal, 2017)
Background: Cardiopulmonary bypass has been implicated in causing poor pulmonary gas exchange postoperatively in patients undergoing coronary artery bypass graft (CABG). This nonrandomized prospective study was conducted to determine whether patients undergoing off-pump CABG and thereby avoiding cardiopulmonary bypass will have improved pulmonary functions postoperatively.Method: Sixty patients undergoing elective CABG in the National Institute of Cardiovascular Diseases (NICVD), Dhaka between July 2005 and June 2006 were consecutively selected in the study. Sample was divided into two groups: Group A- off-pump CABG and Group-B on-pump CABG. The test statistics used to analyze the data were descriptive statistics as Chi-square (×2) and Student's t-test.Results: Preoperative arterial blood gas (ABG) analysis showed no significant difference. ABG immediately at ICU on FiO2 1 revealed significantly better gas exchange in off-pump group (PaO2: 296.5±32.4 torr vs 234.8±10.7 torr, p